A review of rate control in atrial fibrillation, and the rationale and protocol for the RATE-AF trial. Issue 7 (20th July 2017) - Kotecha, Dipak; Calvert, Melanie; Deeks, Jonathan J; Griffith, Michael; Kirchhof, Paulus; Lip, Gregory YH; Mehta, Samir; Slinn, Gemma; Stanbury, Mary; Steeds, Richard P; Townend, Jonathan N
Abstract : Background and objective: Atrial fibrillation (AF) is common and causes impaired quality of life, an increased risk of stroke and death as well as frequent hospital admissions. The majority of patients with AF require control of heart rate. In this article, we summarise the limited evidence from clinical trials that guides prescription, and present the rationale and protocol for a new randomised trial. As rate control has not yet been shown to reduce mortality, there is a clear need to compare the impact of therapy on quality of life, cardiac function and exercise capacity. Such a trial should concentrate on the long-term effects of treatment in the largest proportion of patients with AF, those with symptomatic permanent AF, with the aim of improving patient well-being. Design and intervention: The RAte control Therapy Evaluation in permanent Atrial Fibrillation (RATE-AF) trial will enrol 160 participants with a prospective, randomised, open-label, blinded end point design comparing initial rate control with digoxin or bisoprolol. This will be the first head-to-head randomised trial of digoxin and beta-blockers in AF. Participants: Recruited patients will be aged ≥60 years with permanent AF and symptoms of breathlessness (equivalent to New York Heart Association class II or above), with few exclusion criteria to maximise generalisability to routine clinical practice. Outcome measures: The primary outcome is patient-reported quality of life, with secondary outcomes including echocardiographic ventricular function, exercise capacity and biomarkers of cellular and clinical response. Follow-up will occur at 6 and 12 months, with feasibility components to inform the design of a future trial powered to detect a difference in hospital admission. The RATE-AF trial will underpin an integrated approach to management including biomarkers, functions and symptoms that will guide future research into optimal, personalised rate control in patients with AF. Ethics and dissemination: East Midlands-Derby Research Ethics Committee (16/EM/0178); peer-reviewed publications. Trial registration: Clinicaltrials.gov: NCT02391337 ; ISRCTN: 95259705. Pre-results.